2022
DOI: 10.19094/contextus.2022.77949
|View full text |Cite
|
Sign up to set email alerts
|

Explanatory factors of collective competencies in fashion design teams

Abstract: This article aims to identify the explanatory factors of collective competencies in fashiondesign teams using a survey of 22 fashion designers from Santa Catarina. Exploratory factordata analysis and analysis of variance techniques were applied. The results showed fourexplanatory factors: collective spirit, interaction, cooperation, and relationship. Our findingsmade evident how relevant these factors are in the composition and formation of groups,manifesting themselves as descriptive and essential attributes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The authors demonstrated in their research some Human Resources Management practices (communication, training and development, relationship and incentives) that contributed to actions that foster cooperative relationships and the identification of workers with their team and company, stimulating interactions and collective reflections, shared knowledge and team commitment, bringing these professionals closer to the CC (Silva et al , 2021). From the perspective of managing work teams, Silva et al , 2022b approach that CC allows teams to better understand their collective work activities, aiming to improve their performance to contribute to organizational results. People, when thinking and acting collectively, develop shared actions to get involved and engaged in the work, awakening the feeling of belonging and interdependence with other members.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors demonstrated in their research some Human Resources Management practices (communication, training and development, relationship and incentives) that contributed to actions that foster cooperative relationships and the identification of workers with their team and company, stimulating interactions and collective reflections, shared knowledge and team commitment, bringing these professionals closer to the CC (Silva et al , 2021). From the perspective of managing work teams, Silva et al , 2022b approach that CC allows teams to better understand their collective work activities, aiming to improve their performance to contribute to organizational results. People, when thinking and acting collectively, develop shared actions to get involved and engaged in the work, awakening the feeling of belonging and interdependence with other members.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Montezano et al (2019) problematize the discussion on the determinants of the implementation of competency management in federal institutes. Silva et al (2022b) applied ones when researching the explanatory factors of CC in fashion design teams.…”
Section: Theoretical Frameworkmentioning
confidence: 99%